Nomogram development for operative wastewater control - Шатохіна, Юлія Вікторівна (Eastern-European Journal of Enterprise Technologies, 2015)
It was found that some wastewater treatment stages are provided with accurate, but too long control methods of specific indicators. Operative determination of suspended solids concentration allows to define the required coagulant amount at reagent wastewater treatment and prevent further surface water body pollution. The correlation between wastewater indicators such as the suspended solids concentration and transparency, which is used in the paper to construct nomograms was found. The option of the nomogram depends on the selected parameters and auxiliary functions. Two variants of the correlation between wastewater transparency and suspended solids concentration, which provides two versions of the construction algorithm were considered. The construction algorithm of the first nomogram - determination of the suspended solids concentration from wastewater transparency through the inverse transparency function. The construction algorithm of the second nomogram - determination of the suspended solids concentration from wastewater transparency through the intermediate function. Resulted nomogram construction algorithms can be applied to wastewater with a significant correlation between the indicators.